Narrative Development in Adolescence Creating the Storied Self - McLean, Kate C.; Pasupathi, Monisha; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
The need to establish a narrative self reaches an important peak during adolescence as teens work to understand life events and establish their self-identity. The first book to examine narrative development during adolescence in depth, Narrative Development in Adolescence: Creating the Storied Self, focuses on both stable and at-risk youth as they construct, organize, and tell their life stories and link these stories to larger developmental contexts as they grow to maturity. Renowned specialists identify such core skills as reflection, meaning making, and decision making as well as crucial domains, including autonomy and moral agency evolving across normative adolescence, and relate them to the narrative process. Deficits in these key areas are seen in the more contradictory and incoherent stories narrated by delinquent youth, teenage mothers, and victims of war and violence. In addition, these themes are observed as adolescents process and interpret the narratives of others. This volume offers insights into the crucial task of identity development, and explores new possibilities for counseling and therapy. Its authoritative and accessible coverage: Examines the relationships between narrative and developmental outcomes Identifies normative and problematic issues in adolescents across cultures and social backgrounds in the United States, Canada, Germany, the former Yugoslavia, and New Zealand Offers current research on adolescent narrative development, with attention to theoretical bases and methodological issues Discusses the roles of parents, grandparents, and peers in shaping narratives Features case studies of narratives from at-risk youth Includes findings on how early narrative development predicts narrative identifying adolescence Narrative Development in Adolescence is an essential resource for researchers, clinicians, and graduate students in developmental, clinical child, and school psychology as well as allied mental health and education fields. It is a must-have volume for anyone conducting research or working with adolescents to ensure their healthy development and successful transition to adulthood.
Self-Continuity Across Developmental Change in and of Repeated Life Narratives -- Emerging Identities: Narrative and Self from Early Childhood to Early Adolescence -- Patterns of Family Narrative Co-construction in Relation to Adolescent Identity and Well-Being -- Autonomy, Identity, and Narrative Construction with Parents and Friends -- What He Said to Me Stuck: Adolescents$1 (BNarratives of Grandparents and Their Identity Development in Emerging Adulthood -- Life Stories of Troubled Youth: Meanings for a Mentor and a Scholarly Stranger -- Re-storying the Lives of At-Risk Youth: A Case Study Approach -- Constructing Resilience: Adolescent Motherhood and the Process of Self-Transformation -- Negotiating the Meanings of Adolescent Motherhood Through the Medium of Identity Collages -- How Violent Youth Offenders and Typically Developing Adolescents Construct Moral Agency in Narratives About Doing Harm -- Critical Narrating by Adolescents Growing Up in War: Case Study Across the Former Yugoslavia.s
Keywords: Philosophy (General).; Developmental psychology; Psychology; Developmental Psychology; Child and School Psychology; Education (general).